Numerical models of oceans and oceanic processes - Kantha, L. H. (Academic Press, 2000)
@Tease: Foreword by Kirk Bryan, Princeton University.
Keywords: Oceanography -- Mathematical models.; Oceanography -- Computer simulation.; elektronické knihy; electronic books